2020
DOI: 10.1111/liv.14640
|View full text |Cite
|
Sign up to set email alerts
|

Liver steatosis is highly prevalent and is associated with metabolic risk factors and liver fibrosis in adult patients with type 1 Gaucher disease

Abstract: Background and Aims Gaucher disease (GD) is associated with peculiar metabolic abnormalities (ie hypermetabolic state, peripheral insulin resistance, dyslipidaemia), partially reverted by enzyme replacement therapy (ERT) at the expense of weight gain. Such metabolic alterations together with an unhealthy lifestyle acquired by an ageing GD population may favour the development of liver steatosis. We aimed at evaluating the prevalence of significant liver steatosis and at identifying the factors associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The utility of the MAFLD definition has also been shown in patients with other diseases such as hepatitis B, 18 hepatitis C, 19,20 HIV, 21 celiac disease, 22 myotonic dystrophy type 1 (DM1) 23 and Gaucher disease. 24 This all begs the question, why do we not put the debate aside, capitalize on maintaining momentum and progress the field with the only thing that can more evidence. The MAFLD proposal can be the steppingstone for new vigour among clinicians for patient management on the one hand and on the other, to enhance community and other stakeholder engagement for the benefit of patients.…”
Section: Mafld: Now Is the Time To Capitalize On The Momentummentioning
confidence: 99%
“…The utility of the MAFLD definition has also been shown in patients with other diseases such as hepatitis B, 18 hepatitis C, 19,20 HIV, 21 celiac disease, 22 myotonic dystrophy type 1 (DM1) 23 and Gaucher disease. 24 This all begs the question, why do we not put the debate aside, capitalize on maintaining momentum and progress the field with the only thing that can more evidence. The MAFLD proposal can be the steppingstone for new vigour among clinicians for patient management on the one hand and on the other, to enhance community and other stakeholder engagement for the benefit of patients.…”
Section: Mafld: Now Is the Time To Capitalize On The Momentummentioning
confidence: 99%
“…The definition identifies patients with significant hepatic fibrosis, 6,7 cardiovascular disease, 8,9 chronic kidney disease, 7,10 and those who would benefit from an evaluation of genetic risks for fatty liver 11 better than the previous NAFLD criteria. Its utility has also been demonstrated in patients with other diseases such as hepatitis B, 12,13 hepatitis C, 14,15 HIV, 16 coeliac disease 17 and Gaucher disease, 18 in all of which NAFLD cannot be concomitantly diagnosed. Hegarty et al, express their enthusiastic support for the MAFLD definition and indicate that the rationale behind the redefinition of fatty liver disease in adults is equally applicable for children.…”
Section: Mafld: a Game Changer Redefining Fatty Liver Disease For Adults And Childrenmentioning
confidence: 99%
“…Type 1 Gaucher disease generally presenting with visceromegaly, and liver involvement is almost universal and ranges from with or without liver enzymes alterations, to liver fibrosis (Cox et al, 2017). The latest study showed that significant liver steatosis was highly prevalent in type 1 Gaucher disease patients, reaching about 40% (Nascimbeni et al, 2020). Liver steatosis is characterized by the ectopic storage of triglycerides in hepatocytes and featuring metabolic dysfunction-associated fatty liver disease which is strongly associated with the risk of liver fibrosis/cirrhosis (Younossi et al, 2018).…”
Section: The Gc In Liver Fibrosis After Hepatitismentioning
confidence: 99%